Student’s Perceptions About Parental Disputes and Its Effect on Educational Performance (Journal of Asian Development Studies, 2024)
This descriptive study investigated the influence of parental disputes on the educational accomplishment of their offspring, with a specific emphasis on three primary dimensions: academic performance, study motivation, and attitudes toward education. The data obtained from Ghazi University DG Khan (N= 391) students indicates a significant degree of variability in the views held by these individuals. The data reveals that a substantial proportion of participants agree that disputes between parents have a negative impact on their scholastic accomplishments, as shown by an average rating of 2.52 on a five-point Likert scale Moreover, students have reported that they experience a decrease in motivation (mean= 2.59) and develop a negative attitude towards their academic pursuits (mean= 2.82) due to disputes within their parental relationships. The statistical analysis of variance (ANOVA) provides further evidence to support the existence of these variations, demonstrating that there are highly significant differences between groups about all features (p